Cambios sobre la superficie ocular asociados al uso de extensión de pestañas (2023)
Eyelash extensions are a popular aesthetic method, which consists of increasing the volume and lengthening of these ocular annexes for aesthetic purposes. The process consists of superimposing synthetic eyelashes attached with glue to natural eyelashes. This aesthetic procedure can be associated with changes in the ocular microbiota, eyelid and conjunctival infections.